Impact of sea surface temperature on stratiform cloud formation over the North Sea. Issue 9 (4th May 2017) - Fallmann, Joachim; Lewis, Huw; Castillo, Juan M.; Arnold, Alex; Ramsdale, Steven
Abstract: This study presents a numerical simulation assessing the effect of dynamical ocean–atmosphere coupling on the structure of the marine atmospheric boundary layer over the southern North Sea. Using a high‐resolution regional coupled ocean‐atmosphere prediction system, with a coupling frequency of 1 h, a diurnal variation of sea surface temperature simulated by the ocean model is applied to the atmosphere component. This results in a surface warming in the coupled compared to an atmosphere‐only run. Shallow convection initiated by heating of the lower atmosphere by a relatively warmer ocean surface leads local formation of low level clouds between 1300 h and 1700 h in the coupled run. The impact of these clouds in reflecting incoming solar radiation is demonstrated through a relative cooling of the sea surface temperature in the coupled simulation compared to an ocean‐only run forced by an atmosphere‐only run without representation of ocean‐atmosphere interactions. Key Points: A high‐resolution (kilometer scale) regional coupled ocean‐atmosphere prediction system is applied to assess the impact of a dynamically varying ocean on the marine atmospheric boundary layer Diurnal sea surface temperature (SST) variation leads to a warming of the surface in the shallow shelf region of the North Sea during the afternoon Increased shallow convection over a warmer sea surface modifies the structure of the marine atmospheric boundary layer and leads to formation of low level clouds Plain Language Summary: This paper describes a numerical modeling study, where a weather forecasting model is used on a kilometer scale over the North Sea in order to test the impact of the sea surface temperature on local weather phenomena. A new approach is applied, where an atmospheric model is directly coupled to an ocean model and run for a 5 day case study in July 2014. Over the time of the day, the temperature of the surface increases with increasing incoming radiation, heat is transferred from a warm surface to the atmosphere, and low level clouds develop over the North Sea. This effect is not to be seen when applying the atmospheric model alone without feedback to the ocean. Being closer to the observations in this area, the "coupled" model system is considered to improve local weather forecasts in the area of interest.